THE USE OF CRYPTO COINS TO FINANCE TERRORISM - Eda OGUZ; Nildag BASAK CEYLAN; Ayhan KAPUSUZOGLU (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2021)
It is not a coincidence that cryptocurrencies coincide with the date of their release in 2009. As a result of the global crisis experienced in 2008 and the money printing policies of the central banks, inflation created worldwide. Although the inflation experienced did not cause the decrease in trust in money and banks, it was not the only reason that brought the idea of crypto money, but it was largely effective in ensuring the trust of people against cryptocurrencies. The decentralized and transparent structure of cryptocurrencies, low taxation, limited production, and the fact that exchanges are open 24 hours have attracted people to these platforms. The potential of financial markets to integrate with technology also contributes to the fact that it has become so widespread today. Although the technology used in the production and networks of cryptocurrencies is old, the working principle as an is explained in an article published in 2009. Bitcoin (BTC) is the first peer-to-peer and decentralized currency on the blockchain. Therefore, it is the most famous one. Later, many central and decentralized coins and exchanges are created where they are traded. Terrorist organizations develop various camouflage methods to bypass the firewalls created by legal institutions in order to generate income. These earned revenues are converted into other forms of monetary value (for example: digital/cryptocurrency), making it difficult to trace them. In this study, cryptocurrencies, which are frequently referred as the currency of the future and the illegal usage areas of cryptocurrencies will be discussed.